2009
DOI: 10.1002/humu.21046
|View full text |Cite|
|
Sign up to set email alerts
|

BAK1 gene variation and abdominal aortic aneurysms

Abstract: We sought to examine the role of genetics in the multifactorial disease, abdominal aortic aneurysm (AAA), by studying sequence variation in the BAK1 gene (BAK1) that codes for an apoptotic-promoting protein, as chronic apoptosis activation has been linked to AAA development and progression. BAK1 abdominal aorta cDNA from AAA patients and nondiseased individuals were compared with each other, as well as to the BAK1 genomic sequence obtained from matching blood samples. We found specific BAK1 single nucleotide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…In particular, studies have focused on associating single nucleotide polymorphisms (SNPs) with AAA (examples shown in Table 4). 125130…”
Section: 0 Future Prospects Of Aaa Diagnosis and Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, studies have focused on associating single nucleotide polymorphisms (SNPs) with AAA (examples shown in Table 4). 125130…”
Section: 0 Future Prospects Of Aaa Diagnosis and Monitoringmentioning
confidence: 99%
“…On the other hand, genetic studies have great potential in unraveling the mechanisms behind AAA formation. Furthermore, a genetic marker will be present within all nucleated diploid cells (although there is some evidence to suggest that different polymorphisms may be tissue-specific),125 and are thus easily accessed and sampled in a relatively non-invasive manner. Thus, genetic screening may be useful to determine AAA susceptibility in at-risk populations, and this may prompt firm diagnosis through measurement of dynamic biological systems which more actively reflect current aortic phenotype.…”
Section: 0 Future Prospects Of Aaa Diagnosis and Monitoringmentioning
confidence: 99%
“…However, a few recent studies including our own study of BAK1 and abdominal aortic aneurysms (Gottlieb et al 2009) have suggested that it indeed may be more widespread than previously imagined. Indeed, it has been suggested that a number of neurodegenerative diseases, such as amyotrophic lateral sclerosis may be due to somatic mutations occurring during development resulting in highly variable genetic mosaicism (Frank 2010).…”
Section: Evect Of "Minority" Dna Variants On Genetic Paradigmsmentioning
confidence: 94%
“…However, there do appear to be cases where modifications of disease phenotypes are related to RNA editing [27,28]. …”
Section: Introductionmentioning
confidence: 99%